Collaboration network of applied linguistics research articles with different methodological orientations - Amini Farsani, Mohammad; Jamali, Hamid R. (Studies in Second Language Learning and Teaching, 2023)
The current study draws on synthetic techniques and bibliometric analysis to explore the patterns of scientific collaboration in light of methodological orientations. We examined 3,992 applied linguistics (AL) articles published in 18 top-tier journals from 2009 to 2018 and analyzed their methodological orientations and scientific collaboration. Considering that the number of co-authored papers outweighs single-authored counterparts, our results revealed that the overall degree of collaboration for AL journals was moderate-to-high (57.7%). In particular, quantitative studies contained the highest degree of collaboration (66.8%). This was followed by systematic reviews (60.9%), and mixed-methods approach (55.7%). Country-wise, our overall findings further indicated that the United States and the United Kingdom were the two main hubs of collaborative activities for quantitative, qualitative, and mixed-methods research. While the USA was the top country in systematic reviews like all other research approaches, the UK was the fifth country in systematic reviews. As for collaborating authors, our findings demonstrated that the most influential quantitative researchers had collaborated on Natural Language Processing (NLP) and data mining. While the mixed-methods researchers had a tendency to collaborate on conceptual issues subscribing to the language testing and assessment strand, the most productive qualitative researchers had collaborated on L2 writing issues. Implications for applied linguistics research are further discussed.